Resource constraints and bricolage: The moderating role of entrepreneurs’ creativity cognitive style - Tao Shen; Shuxing Chen (Chinese Journal of Population, Resources and Environment)
This study examines the moderating role of entrepreneurs’ creative cognitive styles in the relationship between resource constraints and bricolage. Drawing on insights from cognitive psychology and entrepreneurial research, we explore how divergent and convergent thinking influence the extent to which entrepreneurs engage in bricolage under resource limitations. Bricolage refers to the creative recombination of available resources to address challenges and seize opportunities, a process often adopted by firms facing financial or knowledge constraints. Yet, individual cognitive differences may determine how effectively entrepreneurs can employ bricolage as a strategic response to scarcity. We propose that divergent thinking—the capacity to generate multiple creative solutions and identify novel resource combinations—strengthens the positive association between resource constraints and bricolage. In contrast, convergent thinking, which emphasizes logical analysis and the pursuit of a single optimal solution, weakens this association. To test these propositions, we collected survey data from 183 entrepreneurs in the United States and employed moderated regression analyses to examine the interactions among cognitive styles, resource constraints, and bricolage behaviors. Our findings reveal that divergent thinking significantly enhances the effect of both financial and knowledge constraints on bricolage, enabling entrepreneurs to creatively leverage limited resources. Conversely, convergent thinking appears to diminish the likelihood of engaging in bricolage when resources are scarce. These results highlight the importance of individual cognitive styles in shaping strategic responses to resource scarcity and contribute to a more nuanced understanding of entrepreneurial bricolage. The study offers practical implications for firms operating in resource-constrained environments by suggesting that enhancing divergent thinking abilities may facilitate more effective resource recombination. Future research should investigate additional cognitive factors and employ longitudinal designs to capture the dynamic nature of entrepreneurial decision-making. These insights open new avenues for further innovative entrepreneurial practices.